2014
DOI: 10.4172/2157-2518.s8-009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Induction of Heme Oxygenase-1 Reduces KB Cell Viability:Role of Carbon Monoxide

Abstract: Heme oxygenase-1 (Hmox1) catalyzes the rate-limiting step in heme degradation, releasing iron, carbon monoxide (CO), and biliverdin. The aim of the present study was to investigate Hmox1 as a possible mechanism underlying propolis cytotoxic effects in KB cells. Cells were cultured for 24, 48 and 72 hours and treated with propolis or SnCl 2 , known inducers of Hmox1 protein expression and activity. Propolis and SnCl 2 treatments decreased cell viability and induced Hmox1 expression. Furthermore, propolis increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Epidemiological studies have shown the ability of dietary compounds to act epigenetically against cancer cells and to influence an individual's risk of developing cancer (6). Several natural antioxidants, in particular polyphenols, have been reported to exhibit chemotherapeutic activity both in vivo and in vitro (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown the ability of dietary compounds to act epigenetically against cancer cells and to influence an individual's risk of developing cancer (6). Several natural antioxidants, in particular polyphenols, have been reported to exhibit chemotherapeutic activity both in vivo and in vitro (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%